Revision of Breda and proposal of a new genus (Araneae: Salticidae) - Ruiz, Gustavo R.s.; Brescovit, Antonio D. (Zootaxa, 2013)
The genus Breda Peckham & Peckham, 1894 is revised and nine valid species are redescribed and illustrated. The mono-typic Paradescanso Vellard, 1924 is established as a new junior synonym of the genus. Breda modesta (Taczanowski, 1878) comb. nov. is transferred from Balmaceda Peckham & Peckham. The following synonymies are also established: Paradescanso fallax Vellard, 1924 = Breda apicalis Simon, 1901 syn. nov.; B. quinquedentata Badcock, 1932 = B. api-calis Simon, 1901 syn. nov.; B. leucoprocta Mello-Leitão, 1940 = B. modesta (Taczanowski, 1878) syn. nov.; B. spini-manu (Mello-Leitão, 1941) = B. modesta (Taczanowski, 1878) syn. nov. The females of B. bicruciata (Mello-Leitão, 1943) and B. bistriata (C.L. Koch, 1846) are described and illustrated for the first time, as well as the male of B. lubomi-rskii (Taczanowski, 1878). Both sexes of Breda akypueruna sp. nov. and males of B. nanica sp. nov. and B. paraensis sp. nov., all three from the Amazon, are described and illustrated, increasing the present menmber list up to 13 species. Druzia gen. nov. is proposed to include B. flavostriata Simon, 1901. The Australian “Breda” jovialis (L. Koch, 1879) is tenta-tively transferred to Ocrisiona Simon.